2021
DOI: 10.1088/1755-1315/846/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Antagonist effect of Bacillus spp. against Aspergillus niger CP isolated from cocopeat powder

Abstract: Bacillus spp. are known as potential bacteria as biocontrol agent against fungal phytopathogen, such as Aspergillus niger. The Aspergillus niger can cause many problems, including in agriculture sector. Antagonist activity of 3 bacteria isolates Bacillus sp. KRG, KRT and LDR have been carried out against Aspergillus niger CP. Dual culture method for antagonist assay was performed using streak, disc, and pour plate technique. Result from the disc technique showed that there is no significant antagonist activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The similar specifications of Aspergillus niger was reported by (Gautam and Bhadauria 2012;Kasfi et al 2018;Romsdahl et al 2018;Rodriguez et al 2019;Kumar et al 2020;Šimonovicová et al 2021). Previously, Santoso et al (2021) identified A. niger based on cultural and morphological characteristics, such as black colony, hyaline conidiophore and sterigmata, biseriate conidia. Mahammed and Chala (2014) examined Aspergillus species differentiation based on their cultural features like colony color, texture and margins, as well as the size of conidia and conidiophores.…”
Section: Isolation and Identification Of Fungisupporting
confidence: 77%
“…The similar specifications of Aspergillus niger was reported by (Gautam and Bhadauria 2012;Kasfi et al 2018;Romsdahl et al 2018;Rodriguez et al 2019;Kumar et al 2020;Šimonovicová et al 2021). Previously, Santoso et al (2021) identified A. niger based on cultural and morphological characteristics, such as black colony, hyaline conidiophore and sterigmata, biseriate conidia. Mahammed and Chala (2014) examined Aspergillus species differentiation based on their cultural features like colony color, texture and margins, as well as the size of conidia and conidiophores.…”
Section: Isolation and Identification Of Fungisupporting
confidence: 77%
“…Bacillus strains have been intensively used against Fusarium [15][16][17][18][19] and Aspergillus [20][21][22] species. Also, Bacillus-based biocontrol has been used to decrease mycotoxin contamination in crops [23][24][25].…”
Section: Bacillus In Horticultural Cropsmentioning
confidence: 99%
“…In the present research, B. siamensis LDR isolated from coconut peat was evaluated for its antifungal compounds using an antibiosis assay (Santoso et al 2021a). This Bacillus species has shown antagonistic activity against several fungal pathogens, such as Aspergillus niger (Santoso et al 2021a), Colletotrichum siamense KA (Fadhilah et al 2021), Fusarium sp., Chaetomium globosum InaCC F228, Ganoderma sp. TB 4 (Santoso et al 2021b), A. clavatus, A. flavus, A. tamarii (Pertiwi et al 2021), and C. lunata BM (Safitri et al 2021.…”
Section: Introductionmentioning
confidence: 99%